Analysis of Factors Related to The Quality of Life of Clients with Breast Cancer - Susilawati .; Khatijah .; Basmanelly . (Faculty of Nursing, Universitas Andalas, 2018)
Background: Breast cancer is one of the cancer that can caused death in women. Breast cancer decreased physical or psychological conditions of patient. Patients with breast cancer can negatively impact the quality of life of these patients. Purpose: To analyze of factors related to the quality of life of clients with breast cancer. Method: The samples were 174 clients of breast cancer at November 2015 who met the criteria for inclusion. This research used descriptive correlation method with cross sectional approach. Statistical tests used were Chi square and double Regression Logistic. Results: The result of this research indicated, patients with breast cancer above 50 years old is 64,4%, those not working 83,3%, high school graduated patients 61,5%, married patients 77,0%, 60,9% patients were at stage 4, 72% had income above one million rupiah, and 73% had fair quality of life. Conclusion: There were relationship among ages, job status, education, marriage status, level of cancer, and income with quality of life. The income is dominant factor of all.